The Senate and people of Rome during Late Antiquity (3rd-7th centuries) - Freitas Reis, Gabriel (Romanitas - Revista de Estudos Grecolatinos, 2023)
Book review of: SALZMAN, M. R. The falls of Rome: crises, resilience and resurgence in Late Antiquity. Cambridge; New York: Cambridge University Press, 2021. 462 p.
Keywords: Late Antiquity; Rome; Senate; Resilience; Long term